A novel fuzzy-logic controller-MDsUPQC topology for power quality improvement in multi-feeder distribution system - Mudhavath, Sriramulu Naik; Rao, Lingineni Shanmukha; Sharma, Pidatala Prabhakara; Latha, Sangu Bala Pushpa (Institute of Advanced Engineering and Science, 2024)
In the current situation, the significant usage of massive non-linear functioned power electronic loads has been increased in domestic and industrial applications. The main problem of power-quality (PQ) deterioration in both voltage quality and current quality from nominal values and also damaging the single/multi feeder distribution systems. The major contribution is to alleviate the PQ issues by employing novel multi-devices unified power-quality conditioner (MDsUPQC) topology in a multi-feeder distribution system. This MDsUPQC comprises multiple voltage source inverter (VSI) devices connected with a common direct current-link (DC-link) capacitor which is controlled by a proportional-integral (PI) controller. However, this controller has some technical issues that are not suited for the regulation of common DC voltage at the desired level because of improper selection of gain values. The contribution of this work is proposing an intelligent fuzzy-logic (FL) DC-link controller-driven MDsUPQC device which evidences the intelligent knowledge base for better regulation of PQ issues. The technique and performance of the suggested strategy for PQ improvement, load sharing between feeders, and simulation results are presented with comparative analysis utilizing the MATLAB/Simulink software tool.